Symbols and mental programs: a hypothesis about human singularity. Issue 9 (September 2022) - Dehaene, Stanislas; Al Roumi, Fosca; Lakretz, Yair; Planton, Samuel; Sablé-Meyer, Mathias
Abstract : Natural language is often seen as the single factor that explains the cognitive singularity of the human species. Instead, we propose that humans possess multiple internal languages of thought, akin to computer languages, which encode and compress structures in various domains (mathematics, music, shape…). These languages rely on cortical circuits distinct from classical language areas. Each is characterized by: (i) the discretization of a domain using a small set of symbols, and (ii) their recursive composition into mental programs that encode nested repetitions with variations. In various tasks of elementary shape or sequence perception, minimum description length in the proposed languages captures human behavior and brain activity, whereas non-human primate data are captured by simpler nonsymbolic models. Our research argues in favor of discrete symbolic models of human thought. Highlights: Accounting for human spatial memory requires the postulation of a mental language that can recursively compose primitives of number, space, and repetition with variations. The same language accounts for the human perception of binary auditory sequences. Minimum description length, rather than actual sequence length, predicts human working memory for auditory and visual sequences. When perceiving geometric shapes, humans exhibit a strong geometric regularity effect, which is absent in non-human primates. Multiple languages with similar computational principles but distinct, parallel brain circuits coexist in the human brain.